2014
DOI: 10.1159/000359966
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Status and Cognitive Function in Euthyroid Patients with Early Parkinson's Disease

Abstract: Background: Alterations in thyroid hormone (TH) levels may be related to the pathogenesis of mild cognitive impairment (MCI) and dementia. Cognitive deficits are common in Parkinson's disease (PD) patients. The aim of this study was to investigate whether variations within the normal ranges of thyroid function are related to cognitive function in early PD without dementia. Methods: Eighty-four euthyroid patients with early PD underwent evaluation of their thyroid status, including measures of thyroid-stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…In contrast to our findings, Choi et al conjectured, contrary to our results, that an increase in fT4 may be more closely associated with cognitive impairment because of the significant correlations shown between fT4 concentrations and general cognition and executive function in PD patients [38]. Two studies provided evidence in favor of this hypothesis: one examined pathology and found that higher levels of total and fT4 were associated with a higher risk of Alzheimer's disease, as well as a higher number of neocortical neuritic plaques and neurofibrillary tangles [39,40].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, Choi et al conjectured, contrary to our results, that an increase in fT4 may be more closely associated with cognitive impairment because of the significant correlations shown between fT4 concentrations and general cognition and executive function in PD patients [38]. Two studies provided evidence in favor of this hypothesis: one examined pathology and found that higher levels of total and fT4 were associated with a higher risk of Alzheimer's disease, as well as a higher number of neocortical neuritic plaques and neurofibrillary tangles [39,40].…”
Section: Discussioncontrasting
confidence: 99%
“…We found a statistically significant positive link between our patients' cognitive impairment and TSH levels in the current investigation. Previous research has not been able to establish a meaningful connection between T3 and cognitive performance [38].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This researcher obtained different results with respect to fT4, finding that high normal concentrations of fT4 positively correlated with worse results in the MMSE, and deterioration of the test results by at least 4 scores within two years of observation [31]. Choi et al also noted that a higher concentration of fT4 in individuals with euthyreosis was related with worse results for executive functions [32].…”
Section: Discussionmentioning
confidence: 95%